Pengaruh Model Pembelajaran Discovery Terhadap Hasil Belajar Kognitif Siswa Kelas VII MTs Al-Anshor Ambon - Muhammad Rizal Hardiansyah; Zamrin Jamdin; Hidaya Tehuayo (IAIN Ambon, 2022)
This study aims to determine the effect of discovery learning model on cognitive learning outcomes of class VII students on heat material at MTs Al-Anshor Ambon. The data collection instruments used were tests and observation sheets. The population in this study was class VII MTs Al - Anshor Ambon academic year 2021/2022 which consisted of 2 classes with a total of 19 students. Based on the hypothesis test of the discovery learning model on students' cognitive learning outcomes, the significance value is smaller than the value of , meaning that the H1 hypothesis is accepted. In student learning outcomes which were analyzed using descriptive and inferential statistics, the average value of the experimental class was 100 and the control class was 80 with a standard deviation of 13.31. The results of hypothesis testing using t-test obtained tcount value of 2.616 and at a significant level 0.05 with dk = 17 obtained ttable = 1.740 thus tcount > ttable¬ then H1 is accepted H0 is rejected. This means that there is a significant effect of discovery learning model on cognitive learning outcomes of class VII students on heat material at MTs Al-Anshor Ambon.